“Studying Injured Minds” – The Vietnam Head Injury Study and 40 Years of Brain Injury Research - Raymont, Vanessa; Salazar, Andres; Krueger, Frank; Grafman, Jordan (Frontiers in Neurology, 2011)
The study of those who have sustained traumatic brain injuries (TBI) during military conflicts has greatly facilitated research in the fields of neuropsychology, neurosurgery, psychiatry, neurology and neuroimaging. The Vietnam Head Injury Study (VHIS) is a prospective, long-term follow-up study of a cohort of 1,221 Vietnam veterans with mostly penetrating brain injuries, which has stretched over more than 40 years. The scope of this study, both in terms of the types of injury and fields of examination, has been extremely broad. It has been instrumental in extending the field of TBI research and in exposing pressing medical and social issues that affect those who suffer such injuries. This review summarizes the history of conflict-related TBI research and the VHIS to date, as well as the vast range of important findings the VHIS has established.